Transformation of HR Development Through Performance Evaluation to Enhance Competitive Advantage in the Digital Era - Yuniman Zebua (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Digital transformation demands adaptive HR strategies to sustain organizational performance and achieve competitive advantage. This study investigates how Human Resource (HR) development transforms in the digital era through performance evaluation and its influence on competitive advantage. As digital technologies reshape organizational dynamics, HR strategies must adapt to maintain business performance. The research examines the roles of recruitment and selection, training and development, and compensation management in influencing performance evaluations, which in turn affect competitive advantage. Employing a quantitative descriptive method, data were gathered from 150 respondents across private companies in Medan, Indonesia, using surveys, observations, and interviews. The analysis used purposive sampling and was processed with PLS-SEM via SmartPLS 4.0. Findings indicate that recruitment and selection, as well as training and development, significantly enhance performance evaluation. However, compensation management does not exhibit a meaningful effect. Additionally, performance evaluation strongly contributes to achieving a competitive advantage. These results underscore the need for HR practices to focus on talent acquisition and skills development tailored to digital demands. The study concludes that performance evaluation plays a key mediating role in linking HR functions to strategic business outcomes. Future research should examine how digital tools and artificial intelligence can further support agile and adaptive HR processes.